Statistical optimization characterizations and Eco- friendly synthesis of silica from sugarcane bagasse - Girma Assefa Habte; Tafere Aga Bullo; Yasin Ahmed (Scientific Reports)
Abstract This research explores the synthesis and optimization of Silica have been effectively produced from sugarcane bagasse (SB) using the sol-gel methods. Due to its rich silica content, sugarcane bagasse can be utilized as a viable alternative source for silica synthesis. Employing Central Composite Design, the study systematically varied combustion temperature (500–800 °C), combustion time (2–4 h), and digestion time (1–3 h) to enhance silica yield. The optimal conditions identified were a combustion temperature of 583.48 °C, a combustion time of 3.482 h, and a digestion time of 2.283 h, resulting in a silica yield of 69.6%. Comprehensive characterization of the synthesized silica was conducted through Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Brunauer, Emmett, Teller model (BET) analysis and Thermo-gravimetric Analysis (TGA). XRD results indicated the amorphous nature of the silica, with a broad peak at 22.36°, akin to that of commercial silica. FTIR analysis revealed six characteristic peaks at wavenumbers corresponding to those found in commercial silica, confirming the presence of similar chemical groups. SEM imagery illustrated a disordered arrangement of silica with undefined morphology. The TGA analysis shows high thermal resistivity of silica with only 9% weigh loss at 800 °C. Overall, this study demonstrates that high-quality silica can be produced from sugarcane bagasse with minimal chemical input and energy consumption and highlighting its potential for diverse applications.